STRATEGI REBRANDING KAMPUNG BABAKAN MENJADI KAMPUNG BERKELIR SEBAGAI UPAYA MENINGKATKAN BRAND IMAGE KOTA TANGERANG - Asriyani Sagiyanto; Arilnda Dwi Darmayanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Transformation made by Kampung Bekelir from slum are becoming tourist destination villages in Kota Tangerang, supporting the Tangerang City Government program related to RPJMD and Live City. The purpose of this study was to determine the rebranding strategy of Kampung Babakan to become Kampung Bekelir in an effort to improve the brand image of Tangerang City. The method used in this study is case study research using a qualitative approach. Data collection techniques using observation, interviews, documentation. The results of the research on rebranding strategies in Kampung Bekelir can increase the brand image in Tangerang City, from the brand image that can provide benefits to the community of Kampung Bekelir to improve their standard of living for the better. Brand Image Tangerang City was awakened by the existence of Bekelir Village. People from various regions and even foreign countries are enthusiastic to come to Kampung Bekelir.